The algorithm design for trust in peer-to-peer bitcoin transactions on blockchain/ Irni Eliana Khairuddin - Khairuddin, Irni Eliana (Faculty of Information Management, 2021)
Bitcoin is a cryptocurrency that has created a new revolution in peer-to-peer technology. Built upon decentralised technology known as Blockchain, it supports transparent, fast, cost-effective, and irreversible transactions, without the need for trusting the third-party financial institution. The privacy of Bitcoin users is protected, by the pseudoanonymous transaction. At present, Bitcoin holds the largest market share in cryptocurrency and the Blockchain technology had captured the interest of multi-corporations, such as Microsoft, Dell, and T-Mobile. However, Bitcoins have no legal tender in most and it is even worse with the illicit use by the irresponsible people and the cyber-attacks towards the application. Hence, these are the primary motivation of this study, to design the algorithm for trust in peer-to-peer transaction. The design work was conducted by using a physical blockchain kit, namely BlocKit with 15 Bitcoin Blockchain experienced to explore the opportunity to develop the algorithm.